Trace elements in edible tissues of the veined rapa whelk (Rapana venosa) in the southern Black Sea, Turkiye: sex, monthly, and age variations and human consumer health risk - Bat, Levent; Basusta, Nuri; Oztekin, Aysah; Sahin, Fatih; Arici, Elif; Seyhan, Kadir (Springer Heidelberg, 2023)
Coastal areas face significant pressures from a variety of human activities, owing primarily to population growth in these areas. Human activities produce a variety of contaminants, including trace metals, which are common forms of contamination that enter marine ecosystems. This study was carried out to provide information on trace element concentrations (Hg, Pb, Cd, Cu, and Zn) in the muscles of Rapana venosa (Valenciennes, 1846) available on Sinop coasts of the southern Black Sea and to evaluate the possible risk associated with their consumption. The minimum and maximum values (mg/kg wet weight) of trace elements in the edible tissue of R. venosa decreased in the following order: Zn (1.75-8.53) > Cu (0.41-4.6) > Cd (0.021-0.255) > Pb (0.013-0.037) > Hg (0.010-0.035). The measured levels of all the trace elements in the present study were lower than the limits permitted by the European Community Regulation (EU), Turkish guideline, and the UK Ministry of Agriculture, Fisheries and Food (MAFF). The hazard index value of Hg, Cd, Cu, and Zn for the veined rapa whelk is lower than standard 1, demonstrating that ingestion of this mollusk from the southern Black Sea does not result in overexposure to these contaminants. The risk index value for human cancer risk of Pb for all seasons was found to be insignificant. When comparing the levels of elements in males and females, significant differences were found in some months for all the metals. In general, the trace elements were detected in higher concentrations in females than in males. Both females and males have accumulated less trace elements with increasing age. This study was the first to show the distribution of trace elements as a function of age in R. venosa.
Keywords: Provisional tolerable weekly intake; Estimated daily intake; Target hazard quotient; Hazard index; Risk index